Intertwingled: The Work and Influence of Ted Nelson - Dechow, Douglas R.; Struppa, Daniele C. (History of Computing, 2015)
History of Computing; Computer Appl. in Arts and Humanities; Data Structures; User Interfaces and Human Computer Interaction